2018
DOI: 10.7717/peerj.4889
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variability of Akhal-Teke horses bred in Italy

Abstract: BackgroundThe Akhal-Teke horse (AKH) is native of the modern Turkmenistan area. It was introduced in Italy from 1991 to 2000 mainly as an endurance horse. This paper characterizes the genetic variability of the whole Italian AKH horse population and evaluates their inbreeding level by analyzing microsatellite markers and mitochondrial D-Loop sequences.MethodsSeventeen microsatellite marker loci were genotyped on 95 DNA samples from almost all the AKH horses bred in Italy in the last 20 years. Standard genetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Recently, many studies have been focused on the loss of biodiversity [ 23 , 24 , 25 ] or the increase in deleterious genotypes [ 26 ] caused by such inbreeding (as reviewed in [ 7 ]). In the last 200 years, the inbreeding practice led to the phenotypical expression at homozygous sites of deleterious variants [ 27 ], as highlighted when the coefficients are calculated in order to evaluate the genetic diversity among different horse breeds [ 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 ,…”
Section: Introductionmentioning
confidence: 99%
“…Recently, many studies have been focused on the loss of biodiversity [ 23 , 24 , 25 ] or the increase in deleterious genotypes [ 26 ] caused by such inbreeding (as reviewed in [ 7 ]). In the last 200 years, the inbreeding practice led to the phenotypical expression at homozygous sites of deleterious variants [ 27 ], as highlighted when the coefficients are calculated in order to evaluate the genetic diversity among different horse breeds [ 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 ,…”
Section: Introductionmentioning
confidence: 99%
“…The Akhal-Teke horse is one of the oldest and most famous horse breeds. It is now mainly distributed in Turkmenistan [ 2 ]. Most of the horses have golden chestnut hair, sometimes black or brown.…”
Section: Discussionmentioning
confidence: 99%
“…Today, the Akhal-Teke horse population is slowly declining and is endangered. Currently, the Akhal-Teke is found mainly in Turkmenistan [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, STR HTG7 is worthy of attention. A low number of alleles in HTG7 (four to six alleles) was recorded in local populations as Akhal-Teke [ 12 , 28 ], Lithuanian Horse [ 7 ], Polish Konig Horse [ 29 ], Colonial Spanish Horse [ 30 ], and Sanfratellano Horse [ 8 ] and in a cosmopolitan breed such as Thoroughbred (four alleles) [ 13 , 31 ]. Additionally, in the present study, HTG7 showed a low number of alleles (from a minimum of four to a maximum of six in the different groups) and a decrease in frequencies of some alleles along the time from the first (1975–90) to the last period (2010–19).…”
Section: Discussionmentioning
confidence: 99%
“…The genetic variability of the LH using pedigree data and STR markers has been described in several studies [ 1 , 2 , 3 , 5 , 6 ]. STR markers have been widely used to analyze the genetic diversity and population structure of other both cosmopolitan and local horse breeds [ 7 , 8 , 9 , 10 , 11 , 12 , 13 ]. STRs are used worldwide for routine equine genotyping applied to forensics, parentage, and kinship analysis [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%